Electrochemical Characterisation And Application of Solid Electrodes Chemically Modified With C60- Fullerene, Tetrathiafulvalene and Silicon Polyoxotungstate - Goh, Joo Kheng (2005)
The modified glassy carbon electrodes by adhered microcrystals of fullerene (C60), tetrathiafulvalene (TTF) and a-Keggin silicon polyoxotungstate, has been studied extensively in characterization and application of these modified electrode in mediating some selected compounds such as cysteine, methionine and nitrite ions in the presence of aqueous electrolytes. The use of a glassy carbon electrode modified by adhered microcrystals of fullerene (C60), mediates the oxidation of cysteine in the presence of aqueous potassium containing electrolytes. Under conditions of cyclic voltarnmetry, the potential for the oxidation of cysteine was lowered by approximately 100 mV and current was enhanced significantly relative to the situation prevailing when a bare glassy carbon electrode was used. Additional mediation occurs when the potential range covered includes that of C60/C60n-r edox couples. The sensitivity under condition of cyclic voltarnrnetry was significantly dependent on pH, temperature and C60 dosage. Excellent analytical and recovery data were obtained with vitamin pill, cassamino acid (hydrolyzed casein) and for a range of beverages. The usefulness of a C60-fullerene modified gold (Au) electrode was extended in mediating the oxidation of methionine in the presence of potassium ions electrolyte. During cyclic voltarnrnetry, an oxidation peak of methionine appearing at +I000 mV vs. AgIAgC1 was observed. The oxidation current of methionine was enhanced by about 2 times using a modified gold electrode. The current enhancement was significantly dependent on pH, temperature and C60 dosage. The variation of scan rate study shows that the system undergoes diffusion-controlled process. Then, diffusion coefficient and rate constant of methionine were determined using hydrodynamic method (rotating disk electrode) with values of 1.1 1 x 10.' cm2 i' and 0.0026 cm s-I respectively for unmodified electrode while the values of diffusion coefficient and rate constant of methionine using C60 modified Au electrode were 5.67 x cm2 i1 and 0.0021 cm s-I respectively. Excellent analytical and recovery data were obtained with root beer beverage.Tetrathiafulvalene modified glassy carbon electrode has been characterized and been applied in the determination of L-cysteine at the potential of +800 mV vs. Ag/AgCl. It has shown to catalyze the oxidation peak of cysteine in the alkaline buffer solution under cyclic voltammetry conditions. The sensitivity of tetrathiafulvalene modified electrode was found to be dependent on pH and dosages of varying concentration of TTF in acetonitrile. Excellent analytical and recovery rates also has been obtained using vitamin pills and root beer syrup either with known amount of cysteine or added deliberately into the samples. The voltammetric reduction of a form of Keggin silicon polyoxotungstate anions, a - [ ~ i ~ ~ h~as0 b~ee~n ]ca~rri-ed out under acidic conditions. The cyclic voltammograms obtained from the solution voltammetry of the Keggin polyoxotungstate anions, a-[~i~12040]s~ho-w ed cyclic voltammogram of a two reversible, one-electron process and a reversible two-electron process in the potential range of +200 mV to -1000 mV (vs. Ag/AgCl). However, only the first reduction process was undertaken in this study. The use of Keggin silicon polyoxotungstate anion, a - [ ~ i ~ ~ ~ 0w4as ~ ] ~ - successfully applied to the synthesis of ruthenium bipyridine silicon polyoxotungstate, [R~(bipy)~]~[a-SivWia~ ~reOd~uc~t]io n of a-[TBA]4[SiW1~040] solvent cast onto the glassy electrode in sulphuric acid. The reduction of nitrite has shown to be catalyzed by [R~(bipy)3]2[a-SiW~~Om~o~di]f ied electrode at lower pH of aqueous sulphuric acid media. Bulk electrolysis technique was employed toreduce a - [ ~ i ~ ~ ~to 0fo4rm~ a] b~lue- s olution of a-[~i~12040T]~he- .r eduction of a - [ ~ i ~ l 2 0 ~to~ a] "- [ ~ i ~ 1 ~w0as ~m~ea]su~red- spectrophotometrically and there was no stable complex formation between a-[~i~12040an]d~ -re duction product of NO< species in the acidic solution. Therefore, the mechanism involving the catalytic effect on a-[siw1204014- in the presence of nitrite suggested that nitrous acid, HN02 has been reduced to a product that possibly containing NO. Beta, P form of Keggin [siw1204014- was found to be less active as compared to the a- [iw1204]